2018
DOI: 10.3390/e21010015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mo, Nb, Ta, Ti, and Zr on Mechanical Properties of Equiatomic Hf-Mo-Nb-Ta-Ti-Zr Alloys

Abstract: Nowadays refractory high-entropy alloys (RHEAs) are regarded as great candidates for the replacement of superalloys at high temperature. To design a RHEA, one must understand the pros and cons of every refractory element. However, the elemental effect on mechanical properties remains unclear. In this study, the subtraction method was applied on equiatomic HfMoNbTaTiZr alloys to discover the role of each element, and, thus, HfMoNbTaTiZr, HfNbTaTiZr, HfMoTaTiZr, HfMoNbTiZr, HfMoNbTaZr, and HfMoNbTaTi were fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…This approach is used in Refs. [8,12,20,29,[54][55][56]. In the second approach, the non-homogeneities of the lattice are considered within the core of dislocations and the solid solution strengthening mechanism is explained by enhanced Peierls-Nabarro stress ( PN ) or friction stress ( f ) of the lattice.…”
Section: Alloy Designmentioning
confidence: 99%
“…This approach is used in Refs. [8,12,20,29,[54][55][56]. In the second approach, the non-homogeneities of the lattice are considered within the core of dislocations and the solid solution strengthening mechanism is explained by enhanced Peierls-Nabarro stress ( PN ) or friction stress ( f ) of the lattice.…”
Section: Alloy Designmentioning
confidence: 99%
“…The CALPHAD method uses a variety of models to explain how the free-energy functions of the different phases are temperature, pressure, and concentration dependence. Three contributions to Gibbs energy from concentration dependency have proved useful for multi-component systems, it is given by G W110 equation ( 33) corresponds to G ex in equation (30). Sundman and Agren 112 introduced this description model at first, which was later modified by Andersson et al 113 Since the Gibbs energy indicates a minimum for a given temperature, pressure, and composition at thermodynamic equilibrium.…”
Section: Prediction Of Solid Solution Phase Via Calphad Approachmentioning
confidence: 99%
“…As a result of their versatility, workability, and environmental safety, HEAs have a wide range of potential applications as structural and functional materials such as thermoelectric materials magnetic materials superconducting. [23][24][25] Contor et al 7 investigated equiatomic multicomponent alloy composition FeCoNiMnCr which exhibited a single FCC solid solution phase while Yeh et al [26][27][28][29][30] additionally explored the different combinations of numerous elements such as Ti, V, Al, Mo, Ta, Zr and Nb which exhibited better mechanical properties compared to the conventional alloy systems. HEAs usually form BCC, FCC solid solution structure, and occasionally HCP structure.…”
Section: Introductionmentioning
confidence: 99%
“…Zýka et al [ 44 ] presented investigations of the room-temperature tensile mechanical properties of selected three- and four-element medium entropy alloys derived from the Hf-Nb-Ta-Ti-Zr system, and they found that it is the five-element HEA alloy that exhibits the best combination of strength and elongation. Tseng et al [ 45 ] aimed to reveal the effects of Mo, Nb, Ta, Ti, and Zr on mechanical properties of equiatomic Hf-Mo-Nb-Ta-Ti-Zr alloys. Another VCrFeTa x W x HEA, which has great high-temperature properties and excellent heat-softening resistance, was studied and recommended by Zhang et al [ 46 ].…”
Section: Mechanical Behaviorsmentioning
confidence: 99%